Social media use as a coping mechanism during the COVID-19 pandemic: A multidimensional perspective on adolescents' well-being - Maftei, Alexandra; Merlici, Ioan-Alex; Dănilă, Oana (Frontiers in Public Health, 2023)
Introduction Social media use was previously characterized as both a maladaptive coping mechanism, and a source of engagement with peers, suggesting an ambivalent effect. The present study explored how adolescents might use social media as a coping mechanism during the COVID-19 pandemic, using a multidimensional perspective on well-being. Methods Our sample consisted of 259 Romanian teenagers aged 11–16 (M = 13.38, SD = 0.93, 57% males). We investigated the potential indirect effect of social media use, i.e., its cognitive, affective, and behavioral dimensions on the relationship between depressive symptoms and adolescents' well-being. Results Across all mediation analyses, our results suggested that social media use positively predicted adolescents' well-being. Given the multidimensional approach to both social media use and well-being, our findings suggested that adolescents' well-being was predicted not only by actual social media use behaviors but also by cognitions related to the expectation of receiving gratification on social media and the intense affective states related to the desire to use social media. Also, our data suggested that adolescents with high levels of depressive symptoms might be more likely to capitalize on social media use and have expectations related to receiving approval from others in the context of social media use. Discussion Depressive symptoms might be more relevant when explaining the cognitive and affective involvement during social media use. However, their ability to predict the actual social media use behaviors may be limited. Furthermore, adolescents that present depressive symptoms might be more prone to use social media, in order to improve their well-being.